Lamotrigine Reduces Stress Symptoms of Chronic Anxiety in the Times of the Covid-19 Natural Catastrophe-A Case Report - Pham, Thuylinh L.; Chrousos, George P.; Merkenschlager, Andreas; Petrowski, Katja; Ullmann, Enrico (Frontiers in Psychiatry, 2021)
The SARS-CoV-2 pandemic has been a worldwide chronic, stress-inducing natural catastrophe associated with increased emotional challenging. Patients with post-traumatic stress disorder (PTSD), self-injury behavior, and obesity are predisposed to aggravation of their symptoms at this time, requiring new therapeutic approaches to balance their disrupted neuro-hormonal stress axis. Here we present our observations of an off-label treatment with lamotrigine in an adolescent girl with PTSD, self-injury behavior and obesity. Lamotrigine was an efficacious pharmaceutical intervention that helped the patient deal with chronic stress and associated anxiety. The results are discussed based on our previous basic research outcomes in animals and humans that focused on the glutamate-cortisol circuits within the limbic brain.